Unlocking the potential: Exploring the opportunities for occupational therapists in cyberpsychology - Haitham Jahrami (SAGE Publishing, 2024)
It has long been established that occupational therapists (OTs) play an important role in assisting clients suffering from a variety of physical and mental health conditions. Cyberpsychology is a relatively new field in medicine that pertains to how technology influences people's mental health and behavior. It covers the effects of social media, online gaming, virtual-augmented reality, artificial intelligence, and other forms of technology on individuals. Among the known psychological phenomena arising from individuals' interactions with digital technologies are cyberbullying and technology addiction. This commentary explores how OTs in the cyberpsychology field can develop personalized interventions to enhance digital well-being and promote healthy technology use.